Pengaruh LMX dan Teamwork terhadap Kinerja Karyawan di PT XYZ - Donny Sutanto Tan; Eko Harry Susanto (Universitas Tarumanagara, 2022)
Organization consists of many or several people. A leader is required to direct, instruct, be a place to ask questions and be examples for subordinates. Leader is an essential-elements in organization. According to LMX theory, a leader shows more inclusive and communicative attitude toward certain members only. The LMX theory emphasizes on the quality of relationships between leaders and members in organization. Organization has variety of processes that require the parties to work together to achieve goals. The company assigns working teams for higher effectiveness can be achieved by teamwork. Teamwork can improve employee performance and has a positive influence in all dimensions of employee performance. This research observes the employees−superiors interaction level, teamwork level and performance based on LMX−teamwork variables. Using quantitative method and likert scale questionnaire unto 82 samples of 103 populations. Result shows that: [1] LMX concepts was applied in the company; [2] the lack of teamwork within the company; [3] The ability of LMX and Teamwork to affect performance is 53.1%; [4] LMX’s coefficient value of 0.730 indicates a positive relationship between LMX and performance. Teamwork’s coefficient value of -0.004 indicates a negative relationship toward Performance. [5] LMX has significant effect for performance; Teamwork has no effect on performance; LMX and Teamwork altogether give a significant influence on Performance.